[Risk-adapted early detection program for prostate cancer 2.0-position paper of the German Society of Urology 2024]. - Michel, Maurice Stephan; Gschwend, Jürgen E.; Wullich, Bernd; Krege, Susanne; Bolenz, Christian; Merseburger, Axel S.; Krabbe, Laura Maria; Schultz-Lampel, Daniela; König, Frank; Haferkamp, Axel; Hadaschik, Boris (Die Urologie, 2024)
BACKGROUND AND OBJECTIVE: Despite the proven effectiveness of organized PSA-based screening in reducing prostate cancer-related mortality, there is currently no program in Germany covered by statutory health insurance. In accordance with the EU Council Decision (2022/0290(NLE)), the German Society of Urology (DGU) has developed a concept for risk-adapted prostate cancer early detection. MATERIALS AND METHODS: Based on a literature review of current screening studies, an algorithm for PSA-based prostate cancer early detection was developed. RESULTS: Risk-adapted prostate cancer screening involves PSA testing in the age group of 45-70 years, followed by PSA-based individual risk stratification and stepwise expansion of diagnostics through magnetic resonance imaging (MRI) to biopsy. While initially up to 2.6 million men will undergo PSA testing, a reduction in these initial examinations to fewer than 200,000 men per year will occur from year four onwards. CONCLUSIONS: The presented algorithm provides clear recommendations for risk-adapted PSA-based early detection for prostate cancer for urologists and patients. The goal is to improve diagnosis of clinically significant prostate cancer, while reducing overdiagnosis and overtreatment.
EVALuna2:594138